Quantitative ontogenetic assessment of connective tissue cell dynamics in the ventricular rat myocardium - Gorbunov A.A.; Tverdokhleb I.V. (Морфологія, 2008)
In this work the dynamics of connective tissue cell number in nonvascular stroma have been studied in different myocardial sites of left and right ventricles in rat hearts during prenatal and early postnatal periods of ontogenesis. The materials of study were hearts of 115 white rats. It has been studied 10 age groups – from 14 days of prenatal development to 20 days of postnatal life. Nonvascular stromal cell quantitative density was estimated by calculation of there nuclei count referred to the square of the cut. During prenatal development it have been studied separately the compact layer and trabecular layer of myocardium, during postnatal period – subendocardial, intramural and subepicardial layers of myocardium. Following pre-sent study a quantitative evaluation of the connective tissue cell number dynamics has been evaluated in ventricular myocardium. The most intensive stromal cell number dynamics in the myocardium have been documented twice – at 14-16 days of embryologic development and at first two weeks after birth. The dynamics in connective tissue cells number during prenatal period had more prominent rate in the compact layer of myocardium in comparison with the trabecular layer. This pattern may point to cellular migration from the developing epicardium toward endocardium. At every stage of cardiogenesis the dynamics in quantitative changes in myocardial connective tissue component correlated with myocardiocyte differentia-tion and microvasculature formation.